Batak Women's Reproductive Health Rights in Determining the Number of Children and Joining the KB Program - Esra Simanjuntak; Sri Rahayu Sanusi; Asfriyati (Britain International for Academic Research (BIAR) Publisher, 2020)
Women's rights based on a patriarchal system which questioned the different biological conditions of women and men are the will of nature (nature), so things such as destiny and nature cannot be changed. Reproductive health is a state of perfect health both physically, mentally and socially and is not merely free from disease or disability in all aspects related to the reproductive system, its functions and processes. Reproductive health problems that occurred in Muara District in 2018, the total coverage of Ante Natal Care visits was 91 out of 299 pregnant women (30.43%). The achievement of use of contraception in 2018 out of 3476 the number of fertile age couples was 1150 people (33.08%) who used family planning and the choice of delivery assistance chosen by the community by a dukun berakak (sibaso). This study aims to explore in depth the perceptions of women's experiences in obtaining the right to determine the number of children and the right to attend the family planning program. This research is a qualitative research with a phenomenological approach. Sampling in this study was conducted by purposive sampling technique. From the suitability and adequacy of the data obtained, there were six informants who participated in this study. The main informant was a Batak woman. Data was obtained through in-depth interviews supplemented with field notes. The results showed that there were a number of women's reproductive health rights that had not yet been fulfilled, namely the right to determine the number of children and birth spacing and the right to attend the KB program. Patriarchal culture influences the position of women in society, women do not know their reproductive health rights. Researcher's suggestion in this study is that health workers have an important role in improving the degree of reproductive health, it is necessary to conduct cross-program and cross-sectoral collaboration with local community leaders to promote women's reproductive rights, because the community is easier to accept input and opinions given by the king custom.